2012
DOI: 10.1155/2012/919106
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nurses Inadequately Assess SAPS II Scores of Very Ill Patients in Real Life

Abstract: Background. Reliable ICU severity scores have been achieved by various healthcare workers but nothing is known regarding the accuracy in real life of severity scores registered by untrained nurses. Methods. In this retrospective multicentre audit, three reviewers independently reassessed 120 SAPS II scores. Correlation and agreement of the sum-scores/variables among reviewers and between nurses and the reviewers' gold standard were assessed globally and for tertiles. Bland and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…SOFA and APACHE II) are weakly or moderately correlated with NAS [37]. In addition, the results of the SAPS 2 and SAPS 3 studies did not always reflect nursing needs [57]. Nevertheless, some NAS items allowed us to describe our sample from a medical point of view (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…SOFA and APACHE II) are weakly or moderately correlated with NAS [37]. In addition, the results of the SAPS 2 and SAPS 3 studies did not always reflect nursing needs [57]. Nevertheless, some NAS items allowed us to describe our sample from a medical point of view (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Another aspect that may have led to this finding was the short training time of the nurses who calculated the severity scores. In the evaluation of reliability of the SAPS II score, the authors observed that nurses who received little training for the application of the scores performed overestimated or underestimated measurements (22) . In accordance with a previous study, the increased workload in nursing was associated with the time of hospitalization of the patient (10) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that whereas the SAPS II is positively associated with mortality in acute renal failure (ARF) (Strand et al, 2010), the SOFA score is widely used in the management of severe sepsis, and can be used to predict the duration of admission and risk of mortality (Siddiqui et al, 2017). Some studies showed that although both the SAPS II and SOFA score could predict the prognosis of septic shock, the SAPS II was a little worse in doing so compared to the SOFA score, which was more reflective of the patient's circulatory system (Kim et al, 2013;Perren et al, 2012). Currently, there are few reports about the application of the SAPS II and SOFA in the prediction of HFRS.…”
Section: Introductionmentioning
confidence: 99%